Safeguarding Creator’s Moral Rights: Unauthorized Color Alterations to the 5-Junction Roundabout Monument Design in Banda Aceh, Indonesia - Ghadamfar Muflih Idroes; Sri Walny Rahayu (Graha Primera Saintifika, 2025)
Moral rights are inherent and non-transferable rights of creators, safeguarding the integrity of their work and their honour or reputation. In 2019, the color of 5-Junction Roundabout Monument in Banda Aceh was repainted without authorization, violating the creators’ moral rights. This study investigates the legal implications of this violation, focusing on the unauthorized colour change of the 5-Junction Roundabout Monument. Using a sociological juridical method and qualitative analysis, it explores the challenges in protecting moral rights for architectural works in Indonesia. The findings show that, despite legal provisions under Article 112 of the Copyright Law, enforcement is hindered by low awareness, weak legal culture, and inefficient systems. The creators have not taken legal action due to limited understanding of their rights. The study recommends that stronger enforcement, increased education, and copyright registration are essential to safeguard creators’ moral rights.